Drug susceptibility in emerging fungal infections: tests with fluconazole, itraconazole, and amphotericin B - Vanessa da Silva Fay; Diana Mara Garcia Rodrigues; Stela Maris Bottin Gonçalves; Tatiana Schaffer Gregianini; Renan Rangel Bonamigo (Sociedade Brasileira de Dermatologia, 2018)
Abstract: The number of new cases of emerging fungal infections has increased considerably in recent years, mainly due to the large number of immunocompromised individuals. The objective of this study was to evaluate the susceptibility of emerging fungi to fluconazole, itraconazole and amphotericin B by disk diffusion method. In 2015, 82 emerging fungi were evaluated in IPB-LACEN/RS and 13 (15.8%) were resistant: 10/52 were from superficial mycoses and 3/30 from systemic mycoses. The data from the study point to the need for permanent vigilance regarding the careful evaluation in the prescription and clinical and laboratory follow-up of patients affected by fungal infections.